2020
DOI: 10.3389/fcell.2020.00181
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Dried Extracellular Vesicles From Adipose-Derived Stem Cells Prevent Hypoxia-Induced Muscle Cell Injury

Abstract: Cellular therapies have tremendous potential for the successful treatment of major extremity wounds in the combat setting, however, the challenges associated with transplanting stem cells in the prolonged field care (PFC) environment are a critical barrier to progress in treating such injuries. These challenges include not only production and storage but also transport and handling issues. Our goal is to develop a new strategy utilizing extracellular vesicles (EVs) secreted by stem cells that can resolve many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 62 publications
0
51
0
Order By: Relevance
“…The safety of exosomes in humans is emphasized by the fact that there have been billions in blood plasma transfusions containing trillions of exosomes over many decades in diverse patients without problems, whereas MSC as cells are difficult to standardize or predict actions of given lots in vivo in patients. On a practical level MSC exos can be freeze‐thawed at least once without toxic cryo‐preservatives, with no lost activity for months to years, and it has been reported that they can be freeze‐dried (El Baradie et al., 2020), for superior storage, allowing on site administration without refrigeration. This can result in uncomplicated use on hospital wards or in poorer countries with low technology medical facilities.…”
Section: Covid 19 Therapy With Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…The safety of exosomes in humans is emphasized by the fact that there have been billions in blood plasma transfusions containing trillions of exosomes over many decades in diverse patients without problems, whereas MSC as cells are difficult to standardize or predict actions of given lots in vivo in patients. On a practical level MSC exos can be freeze‐thawed at least once without toxic cryo‐preservatives, with no lost activity for months to years, and it has been reported that they can be freeze‐dried (El Baradie et al., 2020), for superior storage, allowing on site administration without refrigeration. This can result in uncomplicated use on hospital wards or in poorer countries with low technology medical facilities.…”
Section: Covid 19 Therapy With Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Primary human skeletal myoblasts purchased from ThermoFisher Scientific (Catalog # A11440) were cultured as monolayers in Dulbecco's Modified Eagle Medium (DMEM/High Glucose), supplemented with 5% (v/v) fetal bovine serum (FBS) and 1% (v/v) penicillin/streptomycin (Pen-Strep) as we described previously 41 . The medium was changed after 24 h to discard non-adherent cells.…”
Section: Methodsmentioning
confidence: 99%
“…A stock solution of N-methyl-4-isoleucine cyclosporine NIM-811 (NIM-811; MedChemExpress, NJ, USA) was prepared by dissolving in DMSO at a concentration of 1 mM. As we described previously 41 , different volumes of the stock solution were added to myoblast cultures during the last 20 min of the hypoxia-period to obtain (0–20 µM) final concentrations of NIM-811 in the culture medium (phenol red-free DMEM supplemented with 1% FBS). At the end of the hypoxia period the myoblast cultures were transferred to a normoxic incubator for an additional 2 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More GMP suitable cryopreservation reagents need to be developed for EV preservation. On other hand freeze-dried EVs can be a greater source for long-term storage and therapeutic applications ( El Baradie et al, 2020 ).…”
Section: Challenges In Developing Evs For Clinical Usementioning
confidence: 99%